2019
DOI: 10.1002/fsn3.970
|View full text |Cite
|
Sign up to set email alerts
|

Royal jelly causes hypotension and vasodilation induced by increasing nitric oxide production

Abstract: Among royal jelly’s (RJ) various biological activities, its possible antihypertension and vasorelaxation effects deserve particular attention, but the underlying mechanisms of action remain unclear. Therefore, this study used the spontaneously hypertensive rats (SHR) hypertension model and the isolated rabbit thoracic aorta rings model to explore the mechanisms underlying the hypotension and vasorelaxation effects of RJ. Rats were divided into the following groups ( n = 6): WKY‐control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Therefore, it is assumed that orally administered ACh is mostly degenerated in the process of absorption and blood transport before it reaches the ACh receptor expressed in brain cholinergic synapses and autonomously innervated organs, such as smooth muscles of blood vessels and intestines, pancreas, and LGs. Nevertheless, it has been reported that orally administered RJ has ACh-like effects, such as improvement of Alzheimer’s disease [ 35 ], vasodilation induced by nitric oxide production [ 36 ], and induction of insulin secretion [ 37 ]. Moreover, our previous report showed that RJ had a tear secretion capability via muscarinic acetylcholine receptor (mAChR) signaling induced by intracellular Ca 2+ increase in LGs, which was suppressed by the mAChR antagonist atropine and by inhibitors of phospholipase C and ER-Ca 2+ -ATPase essential enzyme pathways [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is assumed that orally administered ACh is mostly degenerated in the process of absorption and blood transport before it reaches the ACh receptor expressed in brain cholinergic synapses and autonomously innervated organs, such as smooth muscles of blood vessels and intestines, pancreas, and LGs. Nevertheless, it has been reported that orally administered RJ has ACh-like effects, such as improvement of Alzheimer’s disease [ 35 ], vasodilation induced by nitric oxide production [ 36 ], and induction of insulin secretion [ 37 ]. Moreover, our previous report showed that RJ had a tear secretion capability via muscarinic acetylcholine receptor (mAChR) signaling induced by intracellular Ca 2+ increase in LGs, which was suppressed by the mAChR antagonist atropine and by inhibitors of phospholipase C and ER-Ca 2+ -ATPase essential enzyme pathways [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RJ could also increase NO production in cyclic guanosine monophosphate (cGMP) in isolated aortic rings. Anti-hypertensive activities of RJ are associated with NO production while muscarinic receptor agonists produced a vasodilation response by the NO/cGMP pathway and calcium channels [93]. RJ proteins have the potential to inhibit the angiotensin 1-converting enzyme's (ACE) activity produced by the gastrointestinal enzyme hydrolysis and reduce systolic blood pressure in the spontaneously hypertensive rats (SHR) [154].…”
Section: Anti-hypertension Effectmentioning
confidence: 99%
“…A strong correlation between thyroid dysfunction and AD was demonstrated by 14 out of 23 studies [ 203 ]. Research documents an association of thyroid stimulating hormone and free triiodothyronine (T3) with regional cerebral blood flow in patients with MCI and AD [ 204 ].…”
Section: Mechanisms Underlying Effects Of Rj On Cognition and Ad-rmentioning
confidence: 99%